Telhados verdes extensivos : influência da composição do substrato no controle qualitativo e quantitativo das águas pluviais - Scarassatti, Marcella Regyna do Nascimento (2019)
The increase of impervious surface areas caused by urbanization process, coupled with the lack of various urban drainage infrastructure planning needs, promote the environmental degradation and, consequently, the population life quality. In this way, green roofs show positive impact characteristics in the urban drainage scenario, intercepting and absorbing part of the energy reached around it. The recognized positive impacts provided by live plants motivated the seek combination of systems that include living plants as integrated components to built environments structure. However, while rainwater retention and stormwater reduction are the first two functions of green roofs, their pollution potential can affect negatively their use, restricting their ecological and social effects. Thus, the present work evaluated if the use of different substrate composition in extensive green roofs affect the leached water quality and rainwater retention. In this first moment, was evaluated the addition of malt and sugar cane individually mixed with a commercial substrate in a 1:4 volume ratio respectively, and they were compared with the control substrate composed only by the commercial substrate. Eight parameters for leached water quality were analyzed. The results indicated that there was significant reduction just for nitrate and sulfate anions, and the substrate with sugarcane bagasse (C) had better performance in nutrient retention. The control substrate showed better results for turbidity and true color. The other parameters analyzed had no significant difference between treated substrate and control. Simultaneously with this experiment, it was also analyzed the addition of zeolia in a green roof substrate mixture and in a filter system in the experimental modules. Eleven parameters were analyzed for leached water quality and retention. There was a significant reduction in true color parameter, being the FZ substrate better performed. The substrates with zeolite mixture (MZ) and zeolite use filter (FZ) showed no significant differences for electrical conductivity (EC), pH and, chloride and nitrate anions. The water retention average was 68.58% higher for substrate with zeolite addition (MZ) and stored volume average of 23.47 mm. However, statistically there was no significant difference between water retention capacity for the different substrates analyzed. In this study it was more evidenced the relationship between the retention rate and the antecedent dry period, ie, the dry period influenced more than the volume of precipitation, according to Pearson correlation analysis results. In general, the proportion of the mixture may be an important factor for nutrient retention. In terms of performance of leached water quality the results were promising, however, it is recommended to monitor for a longer time in order to verify possible improvements, as well as limitations on the use of malt and sugarcane as well as zeolite on green roof substrates.